Jaminan Perlindungan Hak Pilih dan Kewajiban Negara Melindungi Hak Pilih Warga Negara dalam Konstitusi (Kajian Kritis Pemilu Serentak 2019) - Felani Ahmad Cerdas; Hernadi Afandi (Faculty of Law, Universitas Pattimura, 2019)
Human rights are a fundamental right that has been carried out by a human being while guarantees in the state in protection and regulation must be guaranteed in a fundamental law, namely the constitution of a country in Indonesia itself in the protection of human rights in Article 1 article (2) Article 28 Article 2 Paragraph (1) Article 6 A (1) Article 9 Paragraph (1) Article 22 (c) In essence the protection of the right to vote and be elected by the state is absolutely done while the implementation is stated in Law No. 39 of 1999 concerning Human Rights In article 23 which reads: everyone is free to choose and and has political beliefs, that means the protection of voting rights and voting has been carried out in the Indonesian state's legal politics in practice the suffrage is implemented by the General Election Commission in implementing the right to vote and be elected this is very difficult because the population system in Indonesia is still inadequate as a result of the right to vote this is not obtained by the citizens themselves.